Reverse sural flap for anteromedial ankle and dorsal foot soft-tissue defect following an injury: A case report. (December 2022) - Mohamed, Abdullahi Yusuf; Ibrahim, Yasin Barkhad; Taşkoparan, Hüseyin; Çi̇çek, Engin İlker; May, Hasan
Abstract: Introduction and importance: Foot and ankle soft-tissue defects constitute a real challenge to reconstructive surgeons because of restricted local soft tissue availability. We report a 28 years old male with a significant soft-tissue defect on the left anteromedial ankle and dorsal foot. Case presentation: A 28 years old male with soft-tissue necrosis on the left anteromedial ankle and dorsal foot, as well as second - fourth metatarsal fractures with gangrene of the first - third phalanx, presented to our hospital 14 days after a traffic accident. He underwent debridement and amputation of the gangrenous fingers. In the second operation, a pin fixation of the metatarsal fractures and the reverse sural flap was performed. The donor site was covered with a split-thickness skin graft. The wounds began to improve significantly on the tenth day after the surgery, and his wounds were gone entirely in the third week. The pins were removed eight weeks after the surgery with the fractures healed. Clinical discussion: Skin grafts are easy and quick to cover open wounds but cannot be applied to cover bare tendons or bone. Local flaps of the distal third of the lower extremity have a limited range of motion and arc of rotation. Free flaps are an acceptable but complex reconstructive surgery that requires long operative time, special instruments, and microsurgical training and are expensive. Conclusion: The reverse sural flap was considered feasible in reconstructing patients with soft-tissue defects of the distal leg, ankle, and foot, especially in resource constraint scenarios. Highlights: The distal part of the lower extremity has a special significance in human function and structural form. Foot and ankle soft-tissue defects are challenging to orthopedic surgeons due to limited local soft tissue availability. The reverse sural flap was considered feasible in reconstructing patients with foot and ankle soft-tissue defects.